2012
DOI: 10.15835/nbha4028246
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Salt Stress-Induced Inhibition of Plantago crassifolia Reproductive Development by Supplemental Calcium or Magnesium

Abstract: In Plantago crassifolia, a moderate halophyte characteristic of borders of salt marshes in the Mediterranean region, reproductive development is more sensitive to high soil salinity than vegetative growth. To investigate the possible role of calcium and magnesium salts in the responses of this species to salt stress, adult plants were submitted over a 2-month period to treatments with 300 mM NaCl-a concentration which affects, but does not completely inhibit seed formation in P. crassifolia-either alone or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…These data support and extend previous studies on the influence of salinity on the vegetative development of this species (Vicente et al 2004). Nonetheless, more recent results indicate that in older plants, salt affects mostly reproductive parameters, such as quantity and quality of flowers and seeds (Grigore et al 2012). Numerous studies have shown that salt tolerance is developmentally regulated, and the responses to salt stress of a given species may be quite diverse at different life cycle stages (Flowers et al 1986;Lauchli and Epstein 1990;Johnson et al 1992;Vicente et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These data support and extend previous studies on the influence of salinity on the vegetative development of this species (Vicente et al 2004). Nonetheless, more recent results indicate that in older plants, salt affects mostly reproductive parameters, such as quantity and quality of flowers and seeds (Grigore et al 2012). Numerous studies have shown that salt tolerance is developmentally regulated, and the responses to salt stress of a given species may be quite diverse at different life cycle stages (Flowers et al 1986;Lauchli and Epstein 1990;Johnson et al 1992;Vicente et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Greenway and Munns, 1980;Grigore et al, 2012;English and Colmer, 2013) showed that supplemental Ca 2+ and Mg 2+ can mitigate the deleterious effects of salt stress. In the experiments present here, additional Ca 2+ to maintain the CAR ≥ 0.035 was provided to avoid Na + induced Ca 2+ deficiency (Kopittke and Menzies, 2005).…”
Section: Screening In Sand Versus Soilmentioning
confidence: 99%
“…Milestone Microwave Laboratory Systems) as detailed by Grigore et al (2012b). Quantification of Na + and K + was performed by a flame photometry Jenway PFP7, and by an atomic absorption spectrometry (Model: Varian SpectrAA 220) for the bivalent cations, at 239.9 nm for Ca 2+ and at 202.6 nm for Mg 2+ .…”
Section: Cation Accumulationmentioning
confidence: 99%
“…A high NaCl concentration in soil is one of the most restrictive environmental factors (osmotic and ionic stress), and only a small category of plants, halophytes, have adapted to survive and complete their biological cycle under such conditions. The exact definition of halophytes is ambiguous and controversial (Grigore et al 2012a, and references therein). Halophytes are generally considered to be plants that can grow and complete their life cycle in habitats with soil salinity above 200 mM NaCl (Flowers et al 1986;Flowers and Colmer 2008).…”
Section: Introductionmentioning
confidence: 99%